The association of health behaviors with quality of life in lymphoma survivors. Issue 2 (28th January 2021) - Pophali, Priyanka A.; Larson, Melissa C.; Rosenthal, Allison C.; Robinson, Dennis; Habermann, Thomas M.; Thanarajasingam, Gita; Call, Timothy; Allmer, Cristine; Farooq, Umar; Maurer, Matthew J.; Yost, Kathleen J.; Cerhan, James R.; et al.
Abstract: The impact of change in health behaviors (physical activity [PA], alcohol and smoking) on quality of life (QOL) in lymphoma survivors is not well understood. We evaluated the associations of health behaviors with QOL domains at diagnosis and at 3-year follow-up (FU3) in 2805 lymphoma survivors. We report clinically significant QOL score differences, defined as scores that exceeded a minimally important difference threshold and were statistically significant. Current smoking was associated with lower QOL at baseline ( p  < 0.01) and at FU3 ( p  < 0.01). Meeting the American Cancer Society PA guidelines was associated with better functional wellbeing and overall QOL at FU3 ( p  < 0.01). An increase in PA from baseline to FU3 was associated with improvement in physical, functional wellbeing and overall QOL at FU3 compared to baseline ( p  < 0.01). Thus, QOL in lymphoma survivors is associated with their health behaviors and active interventions to promote positive lifestyle changes in lymphoma survivors are needed.